The Effectiveness of Schema Mode Therapy on Resilience and Self-Control in Adolescent Girls with a History of Non-Suicidal Self-Injury - Adelnasab, Zahra; Torkan, Hajar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The present study aimed to investigate the effectiveness of schema mode therapy on resilience and self-control in adolescent girls with a history of non-suicidal self-injury.Methods and Materials: The present study employed a quasi-experimental design with a pretest–posttest format and a control group. The statistical population consisted of adolescent girls aged 12 to 18 years with a history of non-suicidal self-injury in Isfahan during 2024. A total of 30 participants were selected using purposive sampling and randomly assigned to experimental and control groups, with 15 participants in each group. Data collection instruments included the Connor and Davidson Resilience Scale (CD-RISC) and the Tangney Self-Control Questionnaire (SCQ). The experimental group participated in 10 weekly 90-minute sessions of schema mode therapy, while the control group received no intervention. Data were analyzed using multivariate analysis of covariance (MANCOVA) in SPSS-26 software.Findings: The findings demonstrated that schema mode therapy had a statistically significant effect on both resilience and self-control in adolescent girls with a history of non-suicidal self-injury. The results of multivariate covariance analysis indicated a significant difference between the experimental and control groups in at least one dependent variable at the posttest stage (p < 0.05). Univariate covariance analysis further revealed that resilience significantly increased in the experimental group compared to the control group (F = 21.749, p = 0.001, η² = 0.465). Additionally, self-control scores significantly improved following the intervention (F = 13.103, p = 0.001, η² = 0.344).Conclusion: The findings of the present study indicate that schema mode therapy is an effective intervention for improving resilience and self-control among adolescent girls with a history of non-suicidal self-injury. By targeting maladaptive schemas, dysfunctional coping modes, and emotional dysregulation, schema mode therapy can enhance adaptive psychological functioning and reduce vulnerability to self-injurious behaviors in adolescents.